PHYTOREMEDIATION POTENTIAL OF NATIVE AND ENDEMIC PLANT SPECIES: A SUSTAINABLE SOLUTION TO SOIL AND WATER POLLUTION - Bawankar, Dimraj Y (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Soil and water pollution pose significant threats to environmental health, biodiversity, and human well-being. Anthropogenic activities such as industrialization, agricultural runoff, and improper waste disposal have contributed to the alarming levels of contaminants, including heavy metals, pesticides, and hydrocarbons. Conventional remediation techniques are often costly, invasive, and generate secondary pollution. Phytoremediation, an eco-friendly and cost-effective alternative, utilizes plants to remove, degrade, or stabilize contaminants in polluted environments. Native and endemic plant species offer promising phytoremediation potential due to their adaptability, resilience to local stressors, and compatibility with regional ecosystems. This paper explores the mechanisms, efficiency, and ecological advantages of employing native and endemic species for phytoremediation. It evaluates their capacity to accumulate or detoxify pollutants, enhance microbial activity, and restore ecosystem services. The paper highlights successful case studies from various regions and addresses challenges such as slow remediation rates and plant toxicity thresholds. Strategies for enhancing phytoremediation efficiency, including genetic improvement and microbial symbiosis, are discussed. The findings suggest that harnessing native and endemic plants for phytoremediation not only mitigates pollution but also promotes biodiversity conservation and sustainable land management. Thus, this approach aligns with global environmental goals and provides a holistic pathway to restoring polluted landscapes.